Development of a new reagent inventory management software in research and clinical laboratories - Cavalcante, Thiago; Vizzoni, Alexandre; Correa Moreira, Danielly; Oliveira, Manoel Marques Evangelista (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Research laboratories and clinical laboratories move, every year, a high number of resources to acquire reagents. However, up to this moment several institutions have no unified system for the management of laboratory reagents in stock, which are essential for the working of these units. Unfortunately, there is currently no free software available to improve stock and reagent replacement plan management in a satisfactory manner. Thus, our objective was to develop and implement a specific platform for the Laboratory Information System (LIS) to control inventory of laboratory reagent kits for the Oswaldo Cruz Foundation (Fiocruz). Being this software developed with open-source technologies, ABC curve, customizable alerts, and application for mobile devices and licensed for open source and free use. We observed a gain in productivity and savings inputs and specialized labor with the development and implementation of the automated platform.